From Problem to Practice: Thai EFL Teacher Narrative on Vocabulary Learning Challenges and Solutions - Fauzun, Zahra Janatunnisa; Gunawan, Yudhie Indra; Putra, Aidil Syah (Jurnal Paedagogy, 2026)
This study aims to explore the experiences of Thai EFL teacher in addressing vocabulary learning challenges within a rural primary school context.. This research employed a qualitative method with a narrative inquiry design. The participant was selected through purposive sampling. Data were collected using semi-structured interviews, classroom observations, and video recordings as research instruments. The data were analyzed using narrative analysis supported by thematic analysis to identify recurring patterns in the teacher’s experiences. The results show that students’ vocabulary learning difficulties are influenced by limited concentration, short memory span, weak foundational literacy, and minimal exposure to English outside the classroom. To address these challenges, the teacher implemented adaptive instructional strategies, including repetition, multimodal input (games, songs, and visual aids), and contextualized learning. The findings also reveal that teacher–student interaction, emotional support, and continuous reflective practice play a significant role in improving vocabulary learning. Overall, the study highlights that effective vocabulary instruction in under-resourced EFL contexts depends on teacher adaptability and contextual awareness. The findings suggest the importance of strengthening reflective and adaptive competencies in teacher education while promoting flexible curriculum support for rural schools.